Continuing Professional Development Strategies: A Model for the Iranian EFL Teachers' Success. (March 2018) - Tabatabaee-Yazdi, Mona; Motallebzadeh, Khalil; Ashraf, Hamid; Baghaei, Purya
Throughout the past decade, evaluating teachers' success has become a crucial issue due to the increased motivation on teacher accountability. In view of that the purpose of the present study is to determine EFL (English as a foreign language) teachers' success in the Iranian institutional context based on students' perspectives. More specifically, the present study surveyed any significant correlation between teachers' practices of continuing professional development (CPD) strategies and teachers' success. For this purpose, a CPD model was suggested and verified using partial least squares structural equation modeling (PLS-SEM), to examine CPD factors contributing to EFL teachers' success. A total of 316 English-major institutional teachers in Iran completed the CPD questionnaire. Besides, about 30% of their students, 828 students, are asked to fill in teachers' success questionnaire, which intended to check students' opinions on how successful they measured their teachers in teaching. Findings specified that practice of CPD strategies had a strong direct predicting power on EFL teachers' success. It was illustrated that "updating" construct strongly affects both "collaborating" and "reflecting." Moreover, "reflecting" moderately influence "collaborating" and "collaborating" intensely affects "decision making." The results, specifically, highlight the fact that one to be a successful teacher in the field of EFL should be a good decision maker in the field too.